Embedded crisis workers help to decompress ED, connect mental health and addiction medicine patients with needed resources. - Medved, Ellie; Turturro, Michael (ED Management, 2014)
To manage a big spike in demand from patients seeking emergency care for mental health (MH) and addiction medicine concerns, staff from the University of Pittsburgh Medical Center-Mercy and Western Psychiatric Institute and Clinic of UPMC have devised a series of interventions aimed at quickly linking these patients with the care and resources they need. The most visible intervention is the addition of embedded crisis workers in the ED who help patients with MH or social needs navigate to more appropriate community resources. • In just one year, the time it takes for a detox patient to be seen in the ED has decreased from one hour to less than 15 minutes, and the time it takes for a patient to be admitted to a detox unit has gone from about 20 hours to six hours. • The percentage of patients admitted for MH or addiction medicine concerns has declined as staff have been able to apply inpatient resources more appropriately. • Administrators say the hospital's clinical decision unit, which had been serving as a holding tank for the crush of MH and addiction medicine patients awaiting inpatient beds, can now be used for its intended purpose, for medical issues related to patients evaluated and treatment in the ED.